Praktik Konservasi Padi Lokal melalui Ingatan Kolektif dan Foodways Toraja: Rice Landrace Conservation Practice through Collective Memory and Toraja Foodways - Ikma Citra Ranteallo; Meredian Alam; Azwar Hadi Nasution; Lala M Kolopaking; Djuara P Lubis; Ervizal A. M. Zuhud; Imanuella R Andilolo (Society, 2020)
Many studies on rice landrace (Oryza sativa sbsp. indica) have been conducted by biodiversity, ethnobotany, and agroecology disciplines. The importance of rice landraces as genetic resources and the basics of human civilizations. Conservation landraces in Tumbang Datu and Pongbembe nowadays are affected by the following socio-cultural constraints: a) decline numbers of local varieties after the regional government-imposed funding to local communities to substitute new-high yield varieties, b) rice rites and landrace conservation are on the brink of extinction. This research explores daily behaviors that contribute to rice landrace conservations through the sociological approach of collective memory and symbolic interaction. Today’s generations use new meanings and symbols of rice derived from collective memories and virtues. Various interviewees practice mnemonic devices (what, why, who, where, when, and how) that reflect foodways. According to Blumer, social structures are networks of interdependence among actors that place conditions on their actions. In these networks, people act and produce symbols and meanings of rice to interpret their situations and to have their own set in a localized process of social interpretation. Moreover, the Toraja language is used as a bridge in communicating the past, present, and future to strengthening collective identity. This research uses a qualitative method to explore rice landrace conservation using open-ended questions, in-depth interviews, and Focus Group Discussions. A free-listing method was followed to gather interviewees’ collective memories of rice landraces. Findings show that a combination of methods, tradition-based conservation, and current scientific-technology-based conservation become a practice for promoting, educating, and stimulating the public and researchers to engage in landraces conservation. These findings suggest that the socio-cultural ecosystem and Blumer’s social network support new networks to deliver science in agricultural innovation policy. The results showed that collective memories and foodways create ways that would benefit rice landrace conservation the most.